Overview on the bonding of reinforced concrete under pristine, corrosive and freeze-thaw conditions. Issue 7 (3rd April 2019) - Pei, Pei; Zheng, Shansuo; Zhang, Yixin; Dong, Liguo
Abstract: The bond-slip behavior at the steel-concrete interface plays a significant role in the performance of reinforced concrete (RC) structures. In the past few decades, there has been a growing interest in the effects of interfacial interaction between concrete and reinforcement, especially for the bond-slip behavior incorporating corrosion penetration and freeze-thaw action. This literature review summarizes the state of the art by presenting a brief description of experimental and numerical investigations on the bond-slip behavior of reinforcing bars embedded in concrete under pristine, corrosive and freeze-thaw conditions. The main objective of this paper is to highlight gaps in existing research and to point out future research trends for further advancing bond-slip research, intended to provide reliable prediction and assessment for existing structures.